2016
DOI: 10.1007/s00294-016-0601-7
|View full text |Cite
|
Sign up to set email alerts
|

Condensin-mediated chromosome organization in fission yeast

Abstract: The importance of the condensin complex for mitotic chromosome organization has been appreciated for over 20 years, although exactly what the chromosomal architecture assembled by condensin is, and how that structure contributes to chromosomal segregation remain largely unclear. Here, we discuss our recent findings on how fission yeast condensin mediates interactions among genes and how condensin-dependent interactions play dual roles in the chromosome territory arrangement during interphase and in mitotic chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Furthermore, condensin-enriched sites preferentially interact with each other, although widespread contacts also extend to parts of chromosomes with less prominent condensin binding. These results are consistent with condensin recruitment to highly specific transcribed genes (D’Ambrosio et al 2008 ; Nakazawa et al 2015 ; Robellet et al 2017 ; Schmidt et al 2009 ; Sutani et al 2015 ), and the condensin-dependent interactions between PolIII transcribed genes in interphase (Hausler et al 2008 ; Iwasaki and Noma 2016 ). Fission yeast condensin not only locates at chromatin domain boundaries, but also promotes fusion of interphase domains to generate larger domains in mitosis (Fig.…”
Section: The Contribution Of Smc Complexes To Chromosome Condensationsupporting
confidence: 72%
“…Furthermore, condensin-enriched sites preferentially interact with each other, although widespread contacts also extend to parts of chromosomes with less prominent condensin binding. These results are consistent with condensin recruitment to highly specific transcribed genes (D’Ambrosio et al 2008 ; Nakazawa et al 2015 ; Robellet et al 2017 ; Schmidt et al 2009 ; Sutani et al 2015 ), and the condensin-dependent interactions between PolIII transcribed genes in interphase (Hausler et al 2008 ; Iwasaki and Noma 2016 ). Fission yeast condensin not only locates at chromatin domain boundaries, but also promotes fusion of interphase domains to generate larger domains in mitosis (Fig.…”
Section: The Contribution Of Smc Complexes To Chromosome Condensationsupporting
confidence: 72%
“…In fission yeast, cohesins and condensins seem to play a major role in maintaining overall chromosome structure [13, 214, 254]. Recent studies revealed surprising roles of condensins in organizing centromeric regions in fission yeast [255, 256]. Thus, Hi-C studies suggest that there is higher-order organization to chromatin, though the precise role of heterochromatin, cohesins, condensins or other scaffolding proteins is still uncertain.…”
Section: Chromatin Interactions Within the Whole Nucleusmentioning
confidence: 99%
“…Despite lacking a synaptonemal complex, fission yeast meiotic chromosomes assemble axes, called linear elements (Olson et al 1978 ; Bähler et al 1993 ; Molnar 2003 ), consisting of proteins which are evolutionarily related to axial/lateral elements of the synaptonemal complex (Lorenz et al 2004 ), and building upon the existing mitotic chromosome axis organization (reviewed in Ding et al 2016 ; Iwasaki and Noma 2016 ). One of these components is Hop1 which, in contrast to other meiotic chromosome axis factors, is conserved on the protein sequence level with homologs from yeast to man (Lorenz et al 2004 ; Rosenberg and Corbett 2015 ).…”
Section: Introductionmentioning
confidence: 99%